H19 promotes cholestatic liver fibrosis by preventing ZEB1‐mediated inhibition of epithelial cell adhesion molecule. Issue 4 (26th August 2017) - Song, Yongfeng; Liu, Chune; Liu, Xia; Trottier, Jocelyn; Beaudoin, Michele; Zhang, Li; Pope, Chad; Peng, Guangyong; Barbier, Olivier; Zhong, Xiaobo; Li, Linheng; Wang, Li
Abstract : Based on our recent finding that disruption of bile acid (BA) homeostasis in mice results in the induction of hepatic long noncoding RNA H19 expression, we sought to elucidate the role of H19 in cholestatic liver fibrosis. Hepatic overexpression of H19 RNA augmented bile duct ligation (BDL)‐induced liver fibrosis, which was accompanied by the elevation of serum alanine aminotransferase, aspartate aminotransferase, bilirubin, and BA levels. Multiple genes related to liver fibrosis, inflammation, and biliary hyperplasia were increased in H19‐BDL versus null‐BDL mice, whereas genes in BA synthesis were decreased. Livers and spleens of H19‐BDL mice showed significant enrichment of CD3+γδ+, interleukin‐4, and interleukin‐17 producing CD4+ and CD8+ immune cell populations. H19 down‐regulated hepatic zinc finger E‐box‐binding homeobox 1 (ZEB1) but up‐regulated epithelial cell adhesion molecule (EpCAM) and SRY (sex determining region Y)‐box 9 expression. Mechanistically, ZEB1 repressed EpCAM promoter activity and gene transcription. H19 RNA impeded ZEB1's inhibitory action by interacting with ZEB1 protein to prevent its binding to the EpCAM promoter. Hepatic overexpression of ZEB1 or knockdown of EpCAM diminished H19‐induced fibrosis; the latter was also prevented in H19 −/− mice. H19 RNA was markedly induced by bile acids in mouse small cholangiocytes and to a lesser extent in mouse large cholangiocytes. The up‐regulation of H19 RNA and EpCAM correlated positively with the down‐regulation of ZEB1 in primary sclerosing cholangitis and primary biliary cirrhosis liver specimens. Conclusion: The activation of hepatic H19 RNA promoted cholestatic liver fibrosis in mice through the ZEB1/EpCAM signaling pathway. (Hepatology 2017;66:1183‐1196).